Microplastic pollution associated with reduced respiration in seagrass (Zostera marina L.) and associated epiphytes - Molin, Jacob Malte; Groth-Andersen, William Emil; Hansen, Per Juel; Kühl, Michael; Brodersen, Kasper Elgetti (Frontiers in Marine Science, 2023)
Seagrasses provide crucial ecosystem services of relevance for the marine environment. However, anthropogenic activities are causing global seagrass decline. Increasing microplastic (MP) concentrations have been recognized as a novel threat to many marine organisms, but their effects on marine plants remain underexplored. Here, we investigate the effects of microplastic (polyethylene (PE) and polypropylene (PP)) exposure on the photosynthesis and respiration of the seagrass Zostera marina L. and its associated epiphytes. Measurements were conducted on seagrass leaves with and without epiphyte cover, as well as on epiphytes scraped off the leaf surface. Net gas exchange and pH drift measurements were used to determine rates of photosynthesis and respiration, as well as the ability of leaves and epiphytes to utilize bicarbonate. In addition, variable chlorophyll fluorescence imaging was employed to quantify the photosynthetic capacity of seagrass leaves. Our results show a limited effect of short-term (14 days) microplastic exposure on seagrass leaves and their associated epiphytes, although the photosynthetic activity and respiration rates were gradually reduced for bare seagrass leaves with increasing microplastic concentrations (25-1000 mg MP L-1). A >50% reduction in dark respiration of bare leaves was found at the highest MP exposure, while respiration rates of leaves with epiphytes and separated epiphytes were reduced by maximally 45 and 30% upon MP exposure, respectively. Short-term microplastic exposure did not alter i) the ability to utilize bicarbonate, ii) the maximum quantum yield of PSII (FV/FM), nor iii) the light utilization efficiency of Z. marina leaves and associated epiphytes. The compensation irradiance decreased for all investigated specimens, and seagrass leaves (with and without epiphytes) were able to retain a positive net oxygen balance throughout all treatments. We speculate that the observed decrease in photosynthetic activity and respiration was caused by leachates from microplastics. Our findings thus indicate that seagrass Z. marina largely possess resilience toward microplastic pollution at its current level.